Stackable micromixer with modular design for efficient mixing over wide Reynold numbers. (February 2022) - Zhu, Shu; Fang, Yaohui; Chen, Yao; Yu, Peiwen; Han, Yu; Xiang, Nan; Ni, Zhonghua
Highlights: A modular designed micromixer contains an input module (IM), several stackable enhancement modules (EMs), and an output module (OM). Special structures including planar split-and-recombine, as well as planar and easily-fabricated 3D concave–convex channels are employed. The numbers of EMs can be adjusted flexibly for accomplishing well mixing effect over wide Re numbers. This micromixer is made of cheap materials using well-established technologies, and can be produced massively. Abstract: Fast and efficient micromixing of different species is crucial in many fields. However, most previous micromixers can only achieve well mixing effects in a narrow Reynold number ( Re ) range, and the 3D micromixers for improved mixing efficiency are difficult to fabricate. To overcome these limitations, we report here a modular designed micromixer that contains an input module (IM), several stackable enhancement modules (EMs), and an output module (OM). Special structures including planar split-and-recombine (P-SAR) channel used for working at low Re, as well as planar and easily-fabricated 3D concave–convex channels used for working at high Re are employed in these modules. Moreover, the numbers of EMs can be increased or decreased flexibly for accomplishing well mixing effect over wide Re numbers. To verify our devices, numerical simulation and experiments are conducted. Under low Re (< 1), EM stacking extends the channel length for molecular diffusion to enhance the species mixing. Under intermediate Re (1–30), species can be well mixed by our micromixers through stacking 1–4 EMs. Under high Re (> 30), our micromixer with only 1 EM can achieve well mixing effect. Therefore, our micromixer can be worked over a wide Re range for efficient mixing than those of previous micromixers. Besides, as each module of our micromixers is made of cheap materials using well-established technologies, our micromixer can be produced massively. We envision the wide application of our micromixer in various fields of material synthesis, chemical, and biological analysis. Graphical abstract: A modular designed and stackable micromixer, containing an input module (IM), several unified enhancement modules (EMs), and an output module (OM). Image, graphical abstract